2017
DOI: 10.18203/2320-6012.ijrms20170062
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of MCQ subtypes with grading of performance among undergraduate students in a preclinical discipline

Abstract: INTRODUCTIONIt is a well-known fact that methods of assessment drives learning and holds utmost important place in medical education. 1 Hence it is very important to use various assessment tools which can test the qualities of a medical student who are going to be professionals. Multiple choice questions (MCQs) based evaluation is one of the commonly used methods of formative assessment of medical students apart from structured short answer questions, long answer questions and practical examination. MCQs are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…high (>65%), middle (50% to 65%) and low score (<50%), on the basis of their total percent marks obtained in theory examination (LSQ+MCQ) and labeled them as high, medium and low achievers as reported by us earlier. 4 The minimum total marks obtained by the students were 31.33% and maximum was 76.25%.…”
Section: Analysis Of Datamentioning
confidence: 87%
See 4 more Smart Citations
“…high (>65%), middle (50% to 65%) and low score (<50%), on the basis of their total percent marks obtained in theory examination (LSQ+MCQ) and labeled them as high, medium and low achievers as reported by us earlier. 4 The minimum total marks obtained by the students were 31.33% and maximum was 76.25%.…”
Section: Analysis Of Datamentioning
confidence: 87%
“…single response, multiple response, reasonassertion & problem based questions on the grade of performance of medical students. 4 Studies have reported higher scores in long essay questions as compared to MCQ due to the fact of bias or more subjective marking schemes of different assessors compared with the more quantitative nature of MCQs. 8,9 However, in our format of examination, LSQ consisted of properly structured long and short questions which minimizes the subjective bias of correction by the examiners and may be the reason for obtaining better scores by the students.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations